Benefits of spontaneous confidence alignment between dyad members - Pescetelli, N; Yeung, N (SAGE Publications, 2022)
In many domains, imitating others’ behaviour can help individuals to solve problems that would be too difficult or too complex for the individuals. In collective decision making tasks, people have been shown to use confidence as a means to communicate the uncertainty surrounding internal noisy estimates. Here, we show that confidence alignment, namely, shifting average confidence between dyad members towards each other, naturally emerges when interacting with others’ opinions. This alignment has a measurable impact on group performance as well as the accuracy of individual members following information exchange. It is suggested that confidence alignment arises among individuals from the necessity of minimising confidence variation arising from task-unrelated variables (trait confidence), while at the same time maximising variation arising from stimulus characteristics (state confidence).